Towards a Typology of Narrative Frustration. - Altshuler, Daniel; Kim, Christina S. (Topoi: An International Review of Philosophy, 2024)
Through imaginative engagement readers of fiction become, to an extraordinary extent, the narrator's 'children': they often submit themselves to the narrator's authority without reserve. But precisely because of that, readers are deeply at a loss when their trust is betrayed. This underscores a core function of fiction, namely to evoke emotional response in the reader. In this paper, we hypothesize how a reader's imaginative engagement can be subjected to narrative frustration due to processing or moral complexity. The types of narrative frustration we consider differ in terms of their sources, and their emotional and behavioral impacts on the reader. Here, we break down these frustrations into their component parts, in an effort to better characterize the different classes of frustrations. We propose that frustrations arise from different combinations of local uncertainty, moral clash and global uncertainty. These sources of frustration in turn explain the reader's emotional response and their consequent reading behavior as they imaginatively engage with fiction.